PENERAPAN METODE PROJECT BASED LEARNING DALAM MENINGKATKAN PEMAHAMAN DAN HASIL BELAJAR SISWA KELAS VII - Setyawan, Danang Budi; Sukomiarti, Sukomiarti; Zulfikri, Zulfikri (IBERS : Jurnal Pendidikan Indonesia Bermutu, 2024)
The learning process is very influences of appropriate learning method that are adapted to the material and condition of thr students. In this research the writer applied the Project Based Learning method which aims to improve students understanding and learning outcomes in Ecosystem material. The sample used in this research were 35 students in class VII of SMPN 4 Tanjungpinang. The results of data analysis, it was obtained the percentage of understanding and student learning outcomes in the learning process without applying the Project Based Learning methode, namely pre-cycle, cycle 1 and cycle 2 had an average 60,85, 75,43, and 90,00. From these result, it can be seen that there is an increasing in understanding and student learning outcome. It means that students are able to understand the biological material about ecosystem. This increasing in learning out comes is caused by the habits of students who have below average abilities to participate in the process of completing good learning. This increase in learning outcomes can be achieved because of activities in the form of planning, implementation, data collection and reflection. Beside the activeness of students in participating in the learning process in the pre-cycle, cycle 1 and cycle 2, and the attitude of collaboration in direct observation of Moringa trees in the school environmens.